Gray divorce : what we lose and gain from mid-life splits - Crowley, Jocelyn Elise, 1970- (University of California Press, 2018)
"After twenty, thirty, or even forty years of marriage, countless vacations together, raising well-adjusted children, and sharing property and finances--what could go wrong? Gray Divorce offers a provocative look at the growing rate of marital splits after the age of 50, showcasing the voices of men and women who are considering, going through, or have undergone one. With empathy and insight, Jocelyn Crowley, who has written widely on family issues, uncovers the reasons for why men and women divorce--and the penalties and benefits that each pay for their choice. From the outside, many may ask why couples in mid-life and readying for retirement choose to make a drastic change in their marital status. Yet nearly 1 out of every 4 divorces is "gray." Crowley sheds light on why divorce occurs--seeing marriage in a different lens, understanding the seismic shift in individual priorities, and the impact of the increase in life expectancy. With a deft eye, she analyzes the experiences of women and men as they go through this life transition--specifically how women are affected economically while men are affected socially. With a realistic yet passionate voice, Crowley shares the personal positive outlooks and the necessary supportive public policies that must take place to best help new divorcees. Engaging and instructive, Gray Divorce is a must-read for anyone interested in contemporary American culture"--Provided by publisher.